Kesiapan Kerangka Hukum Indonesia dalam Menghadapi Ekonomi Digital: Tantangan Administrasi Negara untuk Mengatur, Memungut, dan Mengawasi Pajak Digital - Muhammad Wafi Amrillah; Moh. Imam Gusthomi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study examines the readiness of Indonesia’s legal framework in responding to the rapid growth of the digital economy, which presents new challenges for public administration, particularly in the regulation, collection, and supervision of digital taxation. The shift from conventional to digital transaction patterns has compelled the government to update its regulatory instruments, including the implementation of Value Added Tax on Trade Through Electronic Systems (PPN PMSE) and the alignment with international standards such as OECD Pillar One and Pillar Two. A normative-juridical analysis is employed to assess the coherence between existing regulations and the requirements of effective digital tax governance. The findings indicate that despite notable regulatory progress, several obstacles remain, including normative ambiguities, overlapping policies, and limited institutional capacity to monitor cross-jurisdictional digital transactions. These issues underscore the need to strengthen legal harmonization, modernize tax administration, and enhance international cooperation in order to establish a digital taxation system that is adaptive, transparent, and capable of supporting fiscal sustainability in the digital economy era.